2020
DOI: 10.1039/c9sm02331c
|View full text |Cite
|
Sign up to set email alerts
|

Discrete fluidization of dense monodisperse emulsions in neutral wetting microchannels

Abstract: The rheology of pressure-driven flows of two-dimensional dense monodisperse emulsions in neutral wetting microchannels is investigated by means of mesoscopic lattice simulations, capable of handling large collections of droplets, in the order of several hundreds. The simulations reveal that the fluidization of the emulsion proceeds through a sequence of discrete steps, characterized by yielding events whereby layers of droplets start rolling over each other, thus leading to sudden drops of the relative effecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 62 publications
2
13
1
Order By: Relevance
“…Simulations were performed using a 2D hybrid LBM. A more recent study 29 investigated and confirmed the robustness of this discontinuous behavior. This study reported additional discontinuous jumps in viscosity over a larger parameter range, showing how the discontinuous shear thinning is preserved at lower values of the confinement, defined as the ratio between channel height and droplet radius.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Simulations were performed using a 2D hybrid LBM. A more recent study 29 investigated and confirmed the robustness of this discontinuous behavior. This study reported additional discontinuous jumps in viscosity over a larger parameter range, showing how the discontinuous shear thinning is preserved at lower values of the confinement, defined as the ratio between channel height and droplet radius.…”
Section: Introductionmentioning
confidence: 76%
“…The simulations were performed for a fixed value of the ratio between the channel diameter and the droplet radius. In 2D 29 , it is reported that the effective relative viscosity µ r increases with this ratio. We did not vary this ratio but, we do not expect that the effect of confinement is qualitatively different in 3D.…”
Section: Flow Of Deformable Particlesmentioning
confidence: 90%
“…The present model is able to achieve a positive disjoining pressure, independent of the viscosity ratio between components 1 and 2. This enables the simulation of highly packed droplet emulsions under pressure-driven flows [56,58].…”
Section: Resultsmentioning
confidence: 99%
“…Microfluidic crystals consist of a highly ordered and uniform mesoscale porous matrix, made by dispersion of a dense emulsion of droplets (air bubbles or fluid droplets, such as water) stabilized by a surfactant, embedded in a continuous phase, such as oil [2124]. This soft material is usually produced within microchannels, structures a few dozen micrometres in width and manufactured by soft-lithography techniques [25].…”
Section: Microfluidic Soft Flowing Crystalsmentioning
confidence: 99%